Corporate Da’wa Based on Spiritual Capital: Internalizing the Concept of Ihsan in Corporate Work Culture in Indonesia - Abdul Mujib; Ridwan Rustandi; Asep Iwan Setiawan (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This research analyzed the internalization of the Islamic concept of ihsan as a form of social capital integrated into corporate work culture to strengthen leadership competencies and human resource development. The focus is on implementing spirituality in work culture and identifying institutional da'wa values embedded in management practices. Using a constructivist paradigm and a qualitative case study method, this research explored ihsan within the work culture practiced by the Human Capital Division's Sub-Division of Spiritual Capital Management at PT Telkom. Data was collected through observations, interviews, and document analysis concerning corporate da'wa activities aligned with the spiritual capital approach. The findings revealed a spiritually driven work culture reflected in